Project : case-management in Chaos - Chen, Fong Main (1997)
Drew Ameroid (M) Sdn Bhd usually organized a three days annual sales meeting in a holiday resort after the end of their fiscal year. During the annual sales meeting of Drew Ameroid (M) Sdn Bhd for 1997, the Vice President of Drew Ameroid from U.S. Mr. John Town announced a new incentive scheme named 'Loyalty Bonus' to retain experience employees. The Loyalty Bonus was an addition to the normal bonus scheme. This Loyalty Bonus scheme was payable in 1999 and was in the form of an additional three months' bonus on top of the normal bonus. The normal bonus scheme consisted of two months contractual bonus and the variable performance bonus based on company performance. The Loyalty Bonus was only applicable to employees that had served more than one year. Mr. John Town also announced the restructuring of the company with the appointment of a Sales Manager and a Sales Development Manager. Both of them were promoted from the post of Area Managers. There were three Area Managers prior to the restructuring exercise. The Sales Manager, Mr. Anthony Liew was responsible for the overall sales turnover and profitability of the company while the Sales Development Manager, Mr. Alex Y ong was responsible for securing new major customers and the supply and delivery department. The supply and delivery department handled the all the purchases of the company and responsible for the delivery of customers' purchase orders. It was announced that the remaining Area Manager, Mr. Cliff Tan was to report to the newly promoted Sales Manager, Mr. Anthony Liew.